Reactive arthritis following a Microsporidia infection. (November 2016) - Mason, E; Foster, R; Wray, L; McNulty, A; Donovan, B
Reactive arthritis may be caused by both sexually transmissible and enteric organisms, though Microsporidia is not currently recognised as a causative agent. This case report describes the development of reactive arthritis following Microsporidia infection in an immunocompetent man.